A new unidentified leak detection method based on the EVR ventilation condensate. (July 2017) - Tian, Maolin; Cong, Tenglong; Ma, Zhenhui; Chen, Ronghua; Tian, Wenxi; Qiu, Suizheng; Su, G.H.
Abstract: The management of coolant leakage in a Nuclear Reactor Containment is important to ensure the integrity of the second barrier and the safe operation of a nuclear power plant. In the nuclear plant, several reliable leak detection systems continuously monitored coolant leak. In this paper, we introduced a new unidentified leak detection method based on monitoring the condensate in the ventilation coolers. After built a heat exchanger model of the cooler and introduced the fan model in the commercial CFD code, we validated models and got a reasonable simulation of the leak steam condensate on the cooler. Then we built the detail three-dimensional (3D) PWR containment geometry model (including internal structures and ventilation systems). Based on the detailed flow field in this containment and the moisture condensation theory, we could get the condensate character on the coolers of the EVR ventilation system after unidentified leak. Analyses were carried out to quantify the condensate after the 1.0gpm (gal/min) and 1.5gpm leak at hot leg and cold leg located at the reactor pit and steam generator room. The result indicated that the start condensation time of 1.0gpm leak was about 75min and 45min of 1.5gpm, and the leak location had slight influence on the start condensation time. This work would contribute to a reasonable design of a leakage detection method for the unidentified leak in the containment. Highlights: This study constructed a full CFD model for the traditional II PWR containment. 3D flow field in the containment was analyzed under normal condition. The condensate on the EVR system was monitored after 1.0gpm and 1.5gpm RCPB leak. This new detection method would provide an alternative measure to detect the unidentified leak.